A prime-boost immunization with Tc52 N-terminal domain DNA and the recombinant protein expressed in Pichia pastoris protects against Trypanosoma cruzi infection - Matos, Marina Nadia (2016)
We have previously reported that the N-terminal domain of the antigen Tc52 (NTc52) is the section of the protein that confers the strongest protection against Trypanosoma cruzi infection. To improve vaccine efficacy, we conducted here a prime-boost strategy (NTc52PB) by inoculating two doses of pcDNA3.1 encoding the NTc52 DNA carried by attenuated Salmonella (SNTc52), followed by two doses of recombinant NTc52 expressed in Picchia pastoris plus ODN-CpG as adjuvant. This strategy was comparatively analyzed with the following protocols: (1) two doses of NTc52 + ODN-CpG by intranasal route followed by two doses of NTc52 + ODN-CpG by intradermal route (NTc52CpG); (2) four doses of SNTc52; and (3) a control group with four doses of Salmonella carrying the empty plasmid. All immunized groups developed a predominant Th1 cellular immune response but with important differences in antibody development and protection against infection. Thus, immunization with just SNTc52 induces a strong specific cellular response, a specific systemic antibody response that is weak yet functional (considering lysis of trypomastigotes and inhibition of cell invasion), and IgA mucosal immunity, protecting in both the acute and chronic stages of infection. The group that received only recombinant protein (NTc52CpG) developed a strong antibody immune response but weaker cellular immunity than the other groups, and the protection against infection was clear in the acute phase of infection but not in chronicity. The prime-boost strategy, which combines DNA and protein vaccine and both mucosal and systemic immunizations routes, was the best assayed protocol, inducing strong cellular and humoral responses as well as specific mucosal IgA, thus conferring better protection in the acute and chronic stages of infection.